Normal Ranges of Left Ventricular Strain by Three-Dimensional Speckle-Tracking Echocardiography in Adults: A Systematic Review and Meta-Analysis - Truong, Vien T; Phan, Hoang T; Pham, Khanh N P; Duong, Hoang N H; Ngo, Tam N M; Palmer, Cassady; Nguyen, Tuy T H; Truong, Bao H; Vo, Minh A; Tretter, Justin T; Nagueh, Sherif F; Chung, Eugene S; et al. (Journal of the American Society of Echocardiography, 2019)
Establishing normal values and associated variations of three-dimensional speckle-tracking echocardiography- (3DSTE-) derived left ventricular (LV) strain is necessary for accurate interpretation and comparison of measurements. We aimed to perform a meta-analysis of normal ranges of LV global longitudinal strain (GLS), global circumferential strain (GCS), global radial strain (GRS), and global area strain (GAS) measurements derived by 3DSTE and to identify confounding factors that may contribute to variance in reported measures. The authors searched four databases, PubMed, Scopus, Embase, and Cochrane Library, through January 2019 using the key terms "left ventricular/left ventricle/left ventricles", "strain/deformation/speckle tracking", and "three dimensional/three-dimensional/three-dimension/three dimension/3D". Studies were included if the articles reported LV strain using 3DSTE in healthy normal subjects, either in the control group or comprising the entire study cohort. The weighted mean was estimated by using the random effects model with a 95% CI. Heterogeneity across studies was assessed using the I test. Effects of demographic (age), clinical, and vendor variables were assessed in a metaregression. The National Institutes of Health tools were used to assess the quality of included articles. Publication bias was examined by Begg's funnel plot and Egger's regression test. The search yielded 895 articles. After abstract and full-text screening we included 33 data sets with 2,346 patients for meta-analysis. The reported normal mean values of GLS among the studies varied from -15.80% to -23.40% (mean, -19.05%; 95% CI, -18.18% to -19.93%; I = 99.0%), GCS varied from -15.50% to -39.50% (mean, -22.42%; 95% CI, -20.96% to -23.89%, I = 99.7%), GRS varied from 19.81% to 86.61% (mean, 47.48%; 95% CI, 41.50%-53.46%; I = 99.8%), and GAS varied from -27.40% to -50.80% (mean, -35.03%; 95% CI, -33.19% to -36.87%; I = 99.3%). Software for strain analysis was consistently associated with variations in normal strain values (GLS: P = .016; GCS: P < .001; GRS: P < .001; GAS: P < .001). Variations in the normal ranges across studies were significantly associated with the software used for strain analysis, emphasizing that this factor must be considered in the interpretation of strain data.